Sam Walters twitted another inspiring math tweet. This time it is about *Weyl Algebra*. Roughly speaking Weyl algebra is the free algebra generated by two objects $a$ and $b$ which satisfy the *Heisenberg commutation relation* $$ab-ba=1$$ This commutation relation is originated from the *canonical commutation relation* $$qp-pq=i\hbar 1$$ in quantum mechanics. Here $p$ and $q$ represent the momentum and the position operators. Although it is commonly called Weyl algebra, its idea appears to have originated from P.A.M. Dirac [1] and for that reason it is also called *Dirac’s quantum algebra*. In his tweet, Sam stated three properties regarding Weyl algebra to prove as seen in the screenshot below.

~~So far I have been able to prove the properties (1) and (2).~~ Their proofs follow. ~~If/when I prove the property (3), I will included its proof here as an update.~~

(1) Show that $ab,a^2b^2,\cdots,a^nb^n,\cdots$ all commute with one another.

*Proof*. First we show by induction on $n$ that \begin{equation}\label{eq:commut}(ab)(a^nb^n)=(a^nb^n)(ab)\end{equation} for all $n=1,2,\cdots$. Suppose that \eqref{eq:commut} is true for $n=1,\cdots,k$. \begin{align*}(ab)(a^{k+1}b^{k+1})&=(ab)a(a^kb^k)b\\&=a(ba)(a^kb^k)b\\&=a(ab+1)(a^kb^k)b\\&=a(ab)(a^kb^k)b+a(a^kb^k)b\end{align*} Similarly, we show $$(a^{k+1}b^{k+1})(ab)=a(a^kb^k)(ab)b+a(a^kb^k)b$$ By induction hypothesis, we have $$(ab)(a^{k+1}b^{k+1})=(a^{k+1}b^{k+1})(ab)$$ Hence it completes the proof of \eqref{eq:commut}.

Now we show that \begin{equation}\label{eq:commut2}(a^kb^k)(a^mb^m)=(a^mb^m)(a^kb^k)\end{equation} for all $k,m=1,2,\cdots$. Fix $k$ and we do induction on $m$. Suppose \eqref{eq:commut2} is true for all $m=1,\cdots,l$. \begin{align*}(a^{l+1}b^{l+1})(a^kb^k)&=a^l(ab)b^l(a^kb^k)\\&=a^l(1+ba)b^l(a^kb^k)\\&=(a^lb^l)(a^kb^k)+a^l(ba)b^l(a^kb^k)\end{align*} Similarly we show that $$(a^kb^k)(a^{l+1}b^{l+1})=(a^kb^k)(a^lb^l)+(a^kb^k)a^l(ba)b^l$$ Thus we are done if we can show that $$a^l(ba)b^l(a^kb^k)=(a^kb^k)a^l(ba)b^l$$ For $l=1$, this is clear by \eqref{eq:commut}. Assume that $l>1$. \begin{align*}a^l(ba)b^l(a^kb^k)&=a^lb(ab)b^{l-1}(a^kb^k)\\&=a^lb(1+ba)b^{l-1}(a^kb^k)\\&=(a^lb^l)(a^kb^k)+a^lb^2(ab)b^{l-2}(a^kb^k)\\&=(a^lb^l)(a^kb^k)+a^lb^2(1+ba)b^{l-2}(a^kb^k)\\&=2(a^lb^l)+a^lb^3ab^{l-2}(a^kb^k)\\&=(l-1)(a^lb^l)(a^kb^k)+(a^lb^l)(ab)(a^kb^k)\end{align*} Similarly we show that $$(a^kb^k)a^l(ba)b^l=(l-1)(a^kb^k)(a^lb^l)+(a^kb^k)(a^lb^l)(ab)$$ The induction hypothesis and \eqref{eq:commut} then conclude the proof of \eqref{eq:commut2}.

*Lemma*. \begin{align}\label{eq:commut3}[a^k,b]&=a^kb-ba^k=ka^{k-1}\\\label{eq:commut4}[a,b^k]&=kb^{k-1}\end{align}

*Proof*. We prove only \eqref{eq:commut3} as \eqref{eq:commut4} can be proved similarly. $k=1$ is the commutation relation. Assume that $k>1$. \begin{align*}a^kb-ba^k&=a^{k-1}(ab)-ba^k\\&=a^{-1}(1+ba)-ba^k\\&=a^{k-1}+a^{k-1}ba-ba^k\\&=a^{k-1}+a^{k-2}(ab)a-ba^k\\&=a^{k-1}+a^{k-2}(1+ba)a-ba^k\\&=2a^{k-1}+a^{k-2}ba^2-ba^k\end{align*} Continuing this process we arrive at $$a^kb-ba^k=ka^{k-1}$$

*Short Proof*. One can prove \eqref{eq:commut3} and \eqref{eq:commut4} straightforwardly using the formula $$p(a)b-bp(a)=p'(a)$$ for any polynomial $p$, which is discussed here.

(2) Show that $a^m\ne\lambda 1$ for any integer $m\geq 1$ and scalar $\lambda$.

*Proof*. We prove by contradiction. Suppose that $a^m=\lambda 1$ for some $m\geq 1$ and a scalar $\lambda\ne 0$. If $m=1$, then $ab-ba=0$ so a contradiction. Thus it must be that $m>1$. $[a^m,b]=[\lambda 1,b]=0$. But by \eqref{eq:commut3} $[a^m,b]=ma^{m-1}$. This means that $a^{m-1}=0$ which is a contradiction because $\lambda 1=a^m=a^{m-1}a=0$.

(3) If $a^mb^n=a^pb^q$ ($m,n,p,q\geq 0$) then $m=p$ and $n=q$.

*Proof*. Suppose that $m\ne p$. Without loss of generality one may assume that $m>p$ i.e. $m=p+k$ for some $k\geq 1$. Then $a^mb^n=a^pb^q\Longrightarrow a^p(a^kb^n-b^q)=0$. Weyl algebra has no zero divisors (see for example [2] where it is proved using degree argument) and $a^p\ne 0$ by the property (2). So $a^kb^n-b^q=0$. Since $b^q$ commutes with $b$, so does $a^kb^n$ i.e. $a^kb^{n+1}-ba^kb^n=0$. This implies that $ka^{k-1}=[a^k,b]=0$. A contradiction!. Therefore, $m=p$. One can show that $n=q$ in a similar manner.

**Update: **A twitter user named Long offered a brilliant proof for (1). I reproduce his/her proof here. Let $x=ab$. Then one can easily show by induction on $n$ that $a^nx=(x+n)a^n$ and $xb^n=b^n(x+n)$ for $n=1,2,\cdots$. Now \begin{align*}a^{n+1}b^{n+1}&=a^nxb^n\\&=(x+n)a^nb^n\\&=(x+n)(x+n-1)\cdots (x+1)x\end{align*} This means $a^nb^n$ for all $n=1,2,\cdots$ belong to the commutative subalgebra of Weyl algebra generated by $x=ab$.

*References*:

- P.A.M. Dirac,
*The fundamental equations of quantum mechanics*, Proc. Roy. Soc. A, v.109, pp.642-653, 1925 - S. C. Coutinho, A Primer of Algebraic D-modules, London Mathematical Society Student Texts 33, Cambridge University Press, 1995